Short-scar facelift without temporal flap: a 10-year experience. - Centurión, Patricio (2014)
BACKGROUND: The understanding of facial anatomy and its changes through aging has led to the development of several different facelift techniques that focus on being less invasive and traumatic and, at the same time, providing natural long-lasting results. In this article we describe step by step our facelift technique as it has been done over the past 10 years by the senior author. METHODS: This is a retrospective, descriptive, transversal study in which all patients who underwent a rhytidectomy using our technique from January 2002 to September 2012 were included. All patients were operated on under local anesthesia and superficial conscious sedation. All surgeries were performed by the same surgeon. A complete step-by-step description of the surgical technique can be found in the main article. RESULTS: Between January 2002 and September 2012, a total of 113 patients underwent facelift surgery. Of these, 88.9 % were women and 11.1 % were men. The mean age was 55.3 (± 8.66) years. Primary surgeries represented 80.3 % (n = 94), secondary 18.8 % (n = 22), and tertiary 0.85 % (n = 1). Only one major complication, representing 0.8 %, consisting of a right-sided temporal paresis with 2 months complete recovery was seen. The minor complications rate was 23.1 %. The most common minor complication was hypertrophic/keloid scars which made up 77.8 % of all minor complications. CONCLUSIONS: The technique described provides good and long-lasting aesthetic results with shorter scars, smaller areas of dissection (without temporal and postauricular flaps), and a shorter recovery period. LEVEL OF EVIDENCE V: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors http://www.springer.com/00266 .